Aboriginal and Torres Strait Islander health - Healey, Justin (Issues in society (Balmain, N.S.W.), 2014)
Since 2006, the 'closing the gap' campaign has been pursued in collaboration between government and health, welfare and rights agencies to close the health and life expectancy gap between Indigenous and non-Indigenous Australians within a generation. The health disadvantages experienced by Indigenous Australians are shaped by history and the broader social and economic conditions in which they live; progress has been slow and mixed. This book evaluates the uneven progress being made towards closing the gap. How can Indigenous outcomes be improved across a range of key social and economic determinants of health and wellbeing? Also includes: worksheets and activities, fast facts, glossary, web links, index. Titles in the Issues in Society series are individual resource books which provide an overview on a specific subject comprised of facts and opinions. The information in this resource book is not from any single author, publication or organisation. The unique value of the Issues in Society series lies in its diversity of content and perspectives. The content comes from a wide variety of sources and includes: newspaper reports and opinion pieces, website fact sheets, magazine and journal articles, statistics and surveys, government reports, and literature from special interest groups.